RESPON MASYRAKAT TERHADAP PROGRAM PEMBERDAYAAN PEMERINTAH DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA - Sulistyawati, Harni; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was condectad in the village district of Tenayan Raya Pekanbaru Sail with the formulation of the problems that are (1) what are the forms of empowerment program the poor families in tne village district of Tenayan Raya Sail? (2) How is the response of the society tourads empowerment program in the village district of Tenayan Raya Sail? The pupose of this research is to know of the empowerment program forms a poor family in the village of the Sail to figure out a response toword the govermemnt’s empowerment program in district of Sail. This research was used descriptive quantitative research methods, the sample in this research was took by used the formula by slovin took 10% of the total population. To collect the data of the research by using questioner and observastion the result of this research can be known. The empowerment program forms a poor family in the village of the Sail that is aiming at the fulfillment of basic needs such as the basic food consumtion to the people of rural pool in the prencence of poor rice and cas assistance (BLT), the existence of the neighborhood businesses save program loan (UEK-SP) the existence of program UKM, the existence of a free health service by using card JAMKESMA or JAMKESDA, the presence of smart card, loan, cooperative family program expectations. The society gave a good responde to the government`s empowerment program, but a response to the government`s empowerment program implementation was still less good because in the government`s proverty reduction still tess timety in sharing of poor rice and money direct assistance in cash and leasr the citizens who got smart card.Keywords : Response, Society, Empowerment Program